INTERDISCIPLINARY APPROACHES IN SOCIAL ECONOMIC LAW: A REVIEW OF THE LITERATURE AND SELECTED CASES - Sapta Nur Fallah; Loso Judijanto (CV. Adiba Aisha Amira, 2024)
The interdisciplinary approach in social economic law offers a more holistic and in-depth perspective by combining various disciplines such as law, economics, sociology, and others. Through a literature review and analysis of selected cases, this study finds that the integration of understanding from these various disciplines is crucial in identifying and addressing complex issues facing society and the economy. The study results show that this approach is able to reveal the dynamic interactions between various factors and generate more effective and equitable solutions and policies. Thus, the interdisciplinary approach not only broadens theoretical insights but also provides added value in the practical application of social economic law, which can ultimately benefit all parties involved.